The effect of choice of court agreements on third parties - YEO, Tiong Min (Institutional Knowledge at Singapore Management University, 2024)
The effect of choice of court agreements on the exercise of jurisdiction of the Singapore court between contracting parties at common law has received clarification in Singapore law in recent years. The position is also clear under SICC Rules and the Choice of Court Agreements Act. The effect on third parties is less clear. In this article, the effect of choice of court agreements on the position of third parties under the legal regimes above will be considered, from the perspective of both conflict of laws and the Contracts (Rights of Third Parties) Act in domestic Singapore law. This article has been adapted from a 2022 lecture delivered by Dr Yeo Tiong Min, SC (honoris causa), Yong Pung How Chair Professor of Law, Yong Pung How School of Law, Singapore Management University, as part of the Yong Pung How Professorship of Law Lecture series